1995
DOI: 10.3168/jds.s0022-0302(95)76907-7
|View full text |Cite
|
Sign up to set email alerts
|

Methane and Carbon Dioxide Emissions from Dairy Cows in Full Lactation Monitored over a Six-Month Period

Abstract: Methane and CO2 emissions from a herd of 118 lactating cows were measured directly by continuous monitoring with an infrared gas analyzer from 24 gas sampling locations. A total of 112 d of gas output was recorded between June 1993 and November 1993. Recordings were integrated at .5-h intervals, so that there were 48 data points for each 24-h period. The mean 24-h CH4 emission per cow was 587 +/- 61.3 L; the range was 436 to 721 L. The mean 24-h CO2 emission per cow was 6137 +/- 505 L, and the range was 5032 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
100
3
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 9 publications
22
100
3
5
Order By: Relevance
“…In this study, the CO 2 /CH 4 ratio in breath gases of 15.5 was much higher than those (CO 2 /CH 4 5 9 to 12) reported previously for dairy cows and measured using the open-circuit indirect respiration technique (Kinsman et al, 1995;Sauer et al, 1998), which suggests an obvious overestimation. Higher estimates of total CO 2 emissions in ruminants with the tracer technique (,120%) than those obtained using open-circuit calorimetry have already been reported (Boadi et al, 2002).…”
Section: Sf 6 Tracer Technique and Ch 4 Emission Estimatescontrasting
confidence: 41%
“…In this study, the CO 2 /CH 4 ratio in breath gases of 15.5 was much higher than those (CO 2 /CH 4 5 9 to 12) reported previously for dairy cows and measured using the open-circuit indirect respiration technique (Kinsman et al, 1995;Sauer et al, 1998), which suggests an obvious overestimation. Higher estimates of total CO 2 emissions in ruminants with the tracer technique (,120%) than those obtained using open-circuit calorimetry have already been reported (Boadi et al, 2002).…”
Section: Sf 6 Tracer Technique and Ch 4 Emission Estimatescontrasting
confidence: 41%
“…These can be attributed to differences in diet quality and quantities fed, animal body weight, level of milk production and also differences in methods used for estimating CH 4 emissions in each study. The studies of Kinsman et al (1995), Sauer et al (1998) and Kaharabata et al (2000), which were conducted at the same dairy barn with similar animals and feeding regimes, show similar CH 4 emission efficiency values even though a different method of measuring CH 4 was used in the study of Kaharabata et al (2000). There are limited studies on emission estimates of dairy cattle from other milking herds under different farm conditions in Canada.…”
Section: Measurement Of Methane Emission From Dairy Cattlementioning
confidence: 98%
“…Emissions of CO 2 from dairy housing averaged 1989 kg CO 2 hd is per head) [16]. Kinsman et al [17] reported that the mean daily CH 4 emission per dairy cow (602 kg mean bodyweight) in a tie-stall barn ranged from 373 to 617 g CH 4 AU…”
Section: Greenhouse Gas Inventorymentioning
confidence: 99%